Simulation of blood flow into the popliteal artery to explain the effect of peripheral arterial disease: Investigation the conditions and effects of different foot states during the daily activity of the patient. (October 2020) - Karimipour, Aliakbar; Mokhtari, Hamed; Akbari, Mohammad; Toghraie, Davood; Karimipour, Arash
Highlights: Blood flow is considered as pulsating. Inlet boundary condition is taken as unsteady velocity. Systolic flow occurs when the heart contracts and pumps blood into the arteries. Pressure drop has a linear relationship with the blood HCT. Pressure drop decreases with the inlet velocity reaching its maximum value. Abstract: Background and objective: Peripheral artery disease, one type of atherosclerosis, is a common medical condition in the world that results from plaque build-up in the peripheral blood vessels. The symptoms of this disease are the senses of pain and weakness in outer muscles. Methods: The artery under consideration is called the popliteal artery. In this model, the blood flow is considered as pulsating. Therefore the inlet boundary condition is taken as unsteady velocity, and the outlet boundary condition is taken the outflow. The inlet boundary condition represents the increasing systole flow and the decreasing diastole flow, which occur naturally in blood flow. Systolic flow occurs when the heart contracts and pumps blood into the arteries. The inlet blood flow is in the form of a sine-cosine parabolic profile. Results: The artery bends from the middle at an angle of 45°. As the bending of the artery begins, the flow field also takes a bent form. At this point, the flow bends from the outside of the top wall and enfolds the bottom wall in its bending. For different periods, the popliteal flow is closer to the lower bend when the inlet velocity is more significant. While the top wall experiences a low-intensity region along the bend, the bottom wall experiences the same effect just before and after the bend. As the blood flows along the bend, the flow path becomes significantly curved near the bend, similar to the model. The clotted artery exhibits a large increase in flow due to a reduction in the cross-section as a result of the clotting in half of the artery. The flow before the clotting is not considerably different from the main model of the straight artery. Conclusions: Like shear stress, the pressure drop has a linear relationship with the blood HCT and, hence, the viscosity. The pressure drop decreases with the inlet velocity reaching its maximum value and then increases with the start of the acceleration reduction in the second and third-time steps. This indicates that the pressure drop has a stronger relationship with the acceleration than the inlet velocity.